Etyka brokera ubezpieczeniowego - Wieteska, Stanisław (Annales. Etyka w Życiu Gospodarczym, 2008)
A broker’s activity is one of the elements of insurance mediation. Brokers sell propertyand personal as well as life insurance policies. Apart from the range of duties, the quantitative conditionof distribution channels, the paper also discusses problems of a broker’s professional ethics,which include broadly understood information reliability, activation honesty and assistance in damageliquidation.Signed in 1998, the Sobieszew Charter lays out the norms of ethical broker’s activity in threedimensions: their contacts with clients, mutual contacts and contacts with an insurance company.As well as that, the Charter created the Commission of Professional Ethics, the role of which is settlingconflicts arising in the above-mentioned dimensions.The Charter also established seven main principles of professional ethics including the principleof a fair turnover or that of forming healthy relationships among brokers.The paper investigates the data concerning ethics in broker organizations, the major elements ofwhich are a broker’s impartiality, conducting honest negotiations and the duty of submitting identicalrequests for proposal to insurance companies. The issue of insurance brokerage is not discussed.